2007
DOI: 10.1097/mlg.0b013e31814842f8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Systemic Steroids on Surgical Outcomes in Patients With Chronic Rhinosinusitis With Polyposis: Evaluation With the Novel Perioperative Sinus Endoscopy (POSE) Scoring System

Abstract: The data presented in this study support the practice of administering preoperative systemic steroids to patients undergoing ESS for CRSwP. Furthermore, in the practice of surgeons who provide intensive postoperative care post-ESS, including debridement and medical therapy based on the endoscopic findings, there is evidence to support administering systemic steroids in the postoperative period. The POSE scoring system compares favorably with the LKES and may confer advantages in terms of face/content validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
230
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(235 citation statements)
references
References 197 publications
3
230
1
1
Order By: Relevance
“…However, this study did not show a significant correlation between postoperative endoscopic examination and the CSS (Wright & Agrawal, 2007). Studies evaluating the effect of non-surgical treatment also demonstrated no correlation between RSDI and endoscopic scores (Birch et al, 2001).…”
Section: Rhinoendoscopymentioning
confidence: 39%
See 1 more Smart Citation
“…However, this study did not show a significant correlation between postoperative endoscopic examination and the CSS (Wright & Agrawal, 2007). Studies evaluating the effect of non-surgical treatment also demonstrated no correlation between RSDI and endoscopic scores (Birch et al, 2001).…”
Section: Rhinoendoscopymentioning
confidence: 39%
“…A varying degree of correlation has been shown between improvement of sinonasal symptoms and results from endoscopic examinations after ESS (Giger et al, 2004;Wright & Agrawal, 2007).…”
Section: Rhinoendoscopymentioning
confidence: 99%
“…It was reported that the improvement after FESS is significantly better in patients with severe olfactory dysfunction whereas it is not in patients with mild olfactory dysfunction (Litvack et al, 2009b, Soler et al, 2010. The degree of nasal obstruction, the extent of the rhinosinusitis disease (evaluate by symptom score or CT scan), the coexistence of nasal polyps or allergic rhinitis do not predict the possibility of olfactory improvement after FESS (Bhattacharyya, 2006;Jiang et al, 2009;Wright and Agrawal, 2007). In addition, Jankowski et al (Jankowski and Bodino, 2003) demonstrated that there was a correlation between the improvement of subjective olfactory function after oral corticosteroids given preoperatively and olfactory function 1 year after nazalisation.…”
Section: Peculiar Aspects Of Rhinosinusitis 46mentioning
confidence: 99%
“…This scoring system has since been the instrument of choice to endoscopically evaluate outcomes of interventions in non-neoplastic sinonasal disease prospectively over time in research and clinical practice. Lund and Kennedy, 1995. A newer sinonasal scoring system, the Perioperative Sinus Endoscopy (POSE) scoring system was employed by Wright & Agrawal to evaluate the outcomes in a randomized trial of perioperative systemic steroids on surgical patients with chronic rhinosinusits with polyposis (Wright & Agrawal, 2007). POSE scoring was introduced to enhance face validity and responsiveness to change by providing richer measures of the inflammation in the ethmoid cavity, scarring and obstruction in outflow, as well as evaluation of secondary sinuses and included instructions for baseline assessments ( Wright and Agrawal, 2007. www.…”
mentioning
confidence: 99%
“…Lund and Kennedy, 1995. A newer sinonasal scoring system, the Perioperative Sinus Endoscopy (POSE) scoring system was employed by Wright & Agrawal to evaluate the outcomes in a randomized trial of perioperative systemic steroids on surgical patients with chronic rhinosinusits with polyposis (Wright & Agrawal, 2007). POSE scoring was introduced to enhance face validity and responsiveness to change by providing richer measures of the inflammation in the ethmoid cavity, scarring and obstruction in outflow, as well as evaluation of secondary sinuses and included instructions for baseline assessments ( Wright and Agrawal, 2007. www. intechopen.com In that study, both the Lund -Kennedy Endoscopic score and POSE score were shown to be sensitive to changes over time but the POSE seemed to be more sensitive to subtle changes over time (fig 1) and correlated better with symptom scores.…”
mentioning
confidence: 99%